Study of Ni catalysts on different supports to obtain synthesis gas - Pompeo, Francisco (2005)
Ni catalysts supported on α-Al2O3, ZrO 2 and α-Al2O3-ZrO2 were studied in the synthesis gas reactions (partial oxidation, dry reforming and mixed reforming). The Ni/α-Al2O3-ZrO2 catalyst showed a very good performance in relation to the initial activity and selectivity, comparable to that of the Ni/α-Al2O3 catalyst. Concerning the deactivation, the modification of the α-Al 2O3 supported with ZrO2 leads to a higher stability, due to the strong inhibition of the carbon formation during the reaction. These results suggest that ZrO2 promotes the gasification of adsorbed intermediates, which are precursors of carbon formation. Temperature programmed oxidation, transmission electron microscopy and Raman spectroscopy experiments showed that on Ni/α-Al2O3 catalyst high amounts of graphitic carbon (whisker-like) are deposited during CO2 reforming reaction, while on Ni/α-Al2O3-ZrO 2 lesser amounts of deposited carbon were observed (about one order lower); a fraction of this carbon is of the same nature as that observed on Ni/α-Al2O3 catalyst, while the other fraction is composed of carbon nanotubes, both of single wall and multi wall.